Prezesi, dyrektorzy i urzędnicy: środowisko bankowe II Rzeczypospolitej i PRL - Leszczyńska, Cecylia (Komunizm: System - Ludzie - Dokumentacja, 2023)
The subject of the study is the management and clerical staff (white-collar workers) of banks in the period of the Second Polish Republic and the Polish People’s Republic (until 1970). The purpose of the analysis is to identify the characteristics of these groups (their education, origin, professional competences and social roles). Regarding the continuity of the staff, the time under discussion can be divided into two subperiods, the turning point of which was the years 1947–1953, during which the banking environment was restructured for social engineering reasons. Until 1948, the same personnel from the interwar period continued to serve the banking community. The changes after 1945 only affected the most senior positions, although other employees from the interwar period still remained at senior levels. The processes that took place after 1948 resulted in the expansion of the banking environment, the mass employment of low-skilled workers, and a fall in the average level of education and qualifications. The banking environment became much more diverse, both socially and in terms of income. In both periods, the most senior employees and the majority of office clerks were white-collar workers, and thus, it could be said, members of the Polish intelligentsia.